Mosque-Based Zakat al-Fitr Management: Evidence from Collection and Distribution Practices at Al-Muttaqien Mosque, Indonesia - Agnes Jevi Rialita; Nanda Tiara (Journal of Contemporary Applied Islamic Philanthropy, 2025)
Purpose: This study aims to analyze the mechanisms of collecting and distributing zakat al-fitr at the mosque level through a case study at Al-Muttaqien Mosque in Metro District. Mosque-based zakat management plays a crucial role in ensuring that zakat distribution reaches eligible beneficiaries effectively. However, in practice, several challenges remain, including limitations in the verification of mustahiq and the limited operational resources available to zakat administrators amil. Methodology: This research employs a qualitative approach. Data were collected through semi-structured interviews with the head and members of the Zakat Collection Unit (UPZ), field observations, and documentation of zakat administrative records. The data were analyzed using data reduction, data display, and conclusion drawing techniques. Source triangulation was applied to ensure the validity and reliability of the research findings. Findings: The results show that the collection of zakat al-fitr at Al-Muttaqien Mosque is conducted directly by the zakat committee through coordination with neighborhood leaders (RT). Most muzakki (zakat payers) fulfill their obligations in the form of rice, while a smaller proportion provide cash contributions, which are subsequently converted into rice before being distributed to the eligible mustahiq. The distribution of zakat is primarily directed toward the groups of the poor (fakir), the needy (miskin), and the zakat administrators (amil). The study finds that mosque-based zakat management operates in a participatory manner within the community.